TC Chair Highlight: Anne Benoit of the Technical Community on Parallel Processing (TCPP). (Computer (00189162), 2022)
IEEE Computer Society (CS) technical communities (TCs) are the foundry from which all our technical conferences are built and run. Our TCs attract all kinds of people in the field who come together to plan events, serve volunteer leadership roles, and help define the features and future of these technical spaces. Computer asked Anne Benoit, current chair of the TC on Parallel Processing (TCPP) and associate professor at ENS Lyon (France), to share with CS members the experiences that led her to the role of TC chair and what keeps her engaged in CS activities. In addition, Ananth Kalyanaraman, TCPP vice chair and associate director, Washington State University School of Electrical Engineering and Computer Science (Pullman, WA, USA). Shares his perspective on the qualities and skills that make a great chair.